A New Approach of Multi-Dimensional Single Valued Plithogenic Neutrosophic Set in Multi Criteria Decision Making - S.P. Priyadharshini; F. Nirmala Irudayam (Neutrosophic Sets and Systems, 2021)
In the wider problem-solving process, decision-making requires knowledge to choose the possible and optimum solution in the real time. Decision making become further complicated if the available criteria are more. In this research work our intend is to study the behaviour of Multi-Dimensional Single valued Plithogenic Neutrosophic Sets(MSVPNS) used in multi criteria decision making with multi values of attributes. We also introduce a novel method to find the optimum solution of Single valued Plithogenic Neutrosophic Sets(SVPNS) with its operators. We apply this concept in the field of agriculture which deals with multi values of attribute and obtain a fruitful result for practising agriculture in a successful way.